Aberrant DNA methylation and its regulation of gene expression in airway smooth muscle cells of individuals with asthma - Clifford, Rachel Louise (2023)
Asthma is a chronic airways disease affecting 262 million people worldwide, over 8 million people in the UK. Symptoms include wheezing, breathlessness, chest tightness and coughing, and are truly debilitating. Asthma exacerbations cause more severe versions of these symptom and 1200 people a year die from asthma. There is no cure for asthma. Current treatments aim to alleviate symptoms and prevent exacerbations, but do not prevent, reduce, or reverse the pathological changes in the asthmatic airway. A better understanding of the molecular mechanisms driving asthma pathology will identify new therapeutic targets and drive benefit for patients in the long term.